A nurse-led, preventive, psychological intervention to reduce PTSD symptom severity in critically ill patients: the POPPI feasibility study and cluster RCT - Paul R Mouncey (Health Services and Delivery Research, 2019)
Background: High numbers of patients experience severe acute stress in critical care units. Acute stress has been linked to post-critical care psychological morbidity, including post-traumatic stress disorder (PTSD). Previously, a preventive, complex psychological intervention [Psychological Outcomes following a nurse-led Preventative Psychological Intervention for critically ill patients (POPPI)] was developed by this research team, to be led by nurses, to reduce the development of PTSD symptom severity at 6 months. Objectives: The objectives were to (1) standardise and refine the POPPI intervention, and, if feasible, (2) evaluate it in a cluster randomised clinical trial (RCT). Design: Two designs were used – (1) two feasibility studies to test the delivery and acceptability (to patients and staff) of the intervention, education package and support tools, and to test the trial procedures (i.e. recruitment and retention), and (2) a multicentre, parallel-group, cluster RCT with a baseline period and staggered roll-out of the intervention. Setting: This study was set in NHS adult, general critical care units. Participants: The participants were adult patients who were > 48 hours in a critical care unit, receiving level 3 care and able to consent. Interventions: The intervention comprised three elements – (1) creating a therapeutic environment in critical care, (2) three stress support sessions for patients identified as acutely stressed and (3) a relaxation and recovery programme for patients identified as acutely stressed. Main outcome measures: Primary outcome – patient-reported symptom severity using the PTSD Symptom Scale – Self Report (PSS-SR) questionnaire (to measure clinical effectiveness) and incremental costs, quality-adjusted life-years (QALYs) and net monetary benefit at 6 months (to measure cost-effectiveness). Secondary outcomes – days alive and free from sedation to day 30; duration of critical care unit stay; PSS-SR score of > 18 points; depression, anxiety and health-related quality of life at 6 months; and lifetime cost-effectiveness. Results: (1) A total of 127 participants were recruited to the intervention feasibility study from two sites and 86 were recruited to the RCT procedures feasibility study from another two sites. The education package, support tools and intervention were refined. (2) A total of 24 sites were randomised to the intervention or control arms. A total of 1458 participants were recruited. Twelve sites delivered the intervention during the intervention period: > 80% of patients received two or more stress support sessions and all 12 sites achieved the target of > 80% of clinical staff completing the POPPI online training. There was, however, variation in delivery across sites. There was little difference between baseline and intervention periods in the development of PTSD symptom severity (measured by mean PSS-SR score) at 6 months for surviving patients in either the intervention or the control group: treatment effect estimate −0.03, 95% confidence interval (CI) −2.58 to 2.52; p = 0.98. On average, the intervention decreased costs and slightly improved QALYs, leading to a positive incremental net benefit at 6 months (£835, 95% CI −£4322 to £5992), but with considerable statistical uncertainty surrounding these results. There were no significant differences between the groups in any of the secondary outcomes or in the prespecified subgroup analyses. Limitations: There was a risk of bias because different consent processes were used and as a result of the lack of blinding, which was mitigated as far as possible within the study design. The intervention started later than anticipated. Patients were not routinely monitored for delirium. Conclusions: Among level 3 patients who stayed > 48 hours in critical care, the delivery of a preventive, complex psychological intervention, led by nurses, did not reduce the development of PTSD symptom severity at 6 months, when compared with usual care. Future work: Prior to development and evaluation of subsequent psychological interventions, there is much to learn from post hoc analyses of the cluster RCT rich quantitative and qualitative data. Trial registration: This trial is registered as ISRCTN61088114 and ISRCTN53448131. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 23, No. 30. See the NIHR Journals Library website for further project information.